Avaliação do cultivo de gramíneas na superfície de aterro sanitário, com ênfase para a redução da emissão de metano e dióxido de carbono para a atmosfera - Santos, Gemmelle Oliveira (2012)
An Urban Solid Waste (USW) Experimental Cell (EC) was set up in an unused area of the West Metropolitan Landfill in Caucaia (ASMOC), in the Metropolitan Region of Fortaleza, with the aim of studying the behavior of different grasses planted on its cover layer in order to reduce atmospheric emissions of CO2 and CH4 and for the production of plant biomass. Gas emissions were tested with static flow plates on the normal cover layer (blank) and on the planted areas, in addition to the measurements taken on the landfill drainage. All measurements were made in two different campaigns. The morphogenesis, structural, productive and nutritional features of the Mombasa, Massai, Andropogon, Buffel and Bermuda grasses were evaluated. The area on which the EC was located was studied prior to the seeding, including a survey of the subsoil stratigraphic profile and groundwater levels, a geophysical soil characterization (grain size, Atterberg limits, normal Proctor compaction, water permeability) and fertility. The USW was studied for its gravimetric composition, density and moisture content and its leachate was analyzed from a physical and chemical perspective. The gases emitted by the drainage in the first campaign (C1) were composed on average by 14.7% CO2, 8.0% CH4, 11.4% O2, and 65.9% of other gases. In the second campaign (C2) there was an increase in the concentration (%) of the two main gases of interest (CO2: 0.3 times; CH4: 0.5 times) and a reduction in the concentration of the others (O2: 0.2 times, and other gases 0.1 times), with the following concentrations: CO2 19.0%, CH4 11.8%, O2 8.7%, and 60.4% of other gases. The gas emissions of the normal cover layer (blank) were lower than those of the drainage, showing a certain retention: C1: CO2 11.6%, CH4 6.5%, O2 9.1% and 72.7% of other gases; C2: CO2 14.9%, CH4 9.4%, O2 7.2% and 68.5% of other gases. Regarding the mass flows, there was an increase between the two campaigns (mean values): 2.5 x 10-3 and 3.6 x 10-3 g/m2.s of CH4 (C1 and C2, respectively), and 1.2 x 10-2 and 1.5 x 10-2 g/m2.s of CO2 (also for C1 and C2, respectively). The volumetric flows were the following (mean values): 4.0 x 10-6 and 5.7 x 10-6 m3/m2.s of CH4 (C1 and C2); and 7.0 x 10-6 and 8.8 x 10-6 m3/m2.s of CO2 (C1 and C2). The flows were within the ranges reported in the literature. Regarding the grass crops, it was observed that even though they were planted on a typical landfill soil without any special soil or cultivation treatment, the seeds of all five studied grasses germinated within the expected biological times. These species survived on the soil of the landfill yet presented smaller plant development indicators than those reported in the literature. The negative effect of an extreme soil compaction and low soil fertility contributed to such lower developmental results. Each crop showed a different ability to prevent gas emissions through the cover layer. We present them in descending order (mean values), namely: Mombasa (2.6% and 3.8% of CH4 in C1/C2, and 4.6% and 6.0% of CO2 in C1/ C2); Massai (2.0% and 2.8% of CH4, and 3.5% and 4.5% of CO2); Andropogon (1.1% and 1.5% of CH4, 1.9% and 2.5% of CO2); Bermuda (0.9% and 1.3% of CH4, 1.6% and 2.0% of CO2); and Buffel (0.4% and 0.6% of CH4, 0.5% and 0.6% of CO2). The volumetric and mass flows were lower in the soil planted with Mombasa grass and higher in that planted with Buffel. This was related to the main morphogenesis, structural, nutritional and productive features used in the assessment of crop survival and development.